2011
DOI: 10.1088/1742-6596/298/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Operation of the superconducting RF photo gun at ELBE

Abstract: As the first superconducting RF photo-injector (SRF gun) in practical operation, the SRF gun has been successfully connected to the superconducting linac ELBE at Forschungzentrum Dresden-Rossendorf. The injection with this new gun will improve the beam quality for the users of the radiation source. The SRF gun contains a 3½ cell superconducting accelerating cavity with a frequency of 1.3 GHz. The design is for use of normal conducting photocathodes. At present, caesium telluride photocathodes are applied which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…With regard to the point cloud stitching problem, many works use an ICP algorithm or improved ICP algorithm (Cheng et al, 2016; Yang et al, 2016). However, here, due to the large deviation of the angle of view, the performance of ICP algorithm is not ideal, thus SVD is adopted to calculate the conversion relationship between the two sets of point clouds (Sorkine, 2009; Jung et al, 2015; Raposo et al, 2016). The principle is described firstly from this transform…”
Section: Technology and Implementationmentioning
confidence: 99%
“…With regard to the point cloud stitching problem, many works use an ICP algorithm or improved ICP algorithm (Cheng et al, 2016; Yang et al, 2016). However, here, due to the large deviation of the angle of view, the performance of ICP algorithm is not ideal, thus SVD is adopted to calculate the conversion relationship between the two sets of point clouds (Sorkine, 2009; Jung et al, 2015; Raposo et al, 2016). The principle is described firstly from this transform…”
Section: Technology and Implementationmentioning
confidence: 99%
“…Due to this effect, it turns out that a strong input mismatch paired with a resonance drift makes it infeasible to raise the accelerating gradient by increasing the incident rf power. Therefore, this phenomenon is a serious problem that limits the accelerating gradient in the cavity to very low values [20]. Hence, minor design changes are under investigation that should allow the SRF gun to operate up to the desired electric field strength [19].…”
Section: Geometry Descriptionmentioning
confidence: 99%
“…10, MP was totally suppressed in the case of 100 V and above but even 50 V could be sufficient. However, in practice it has been found that a voltage up to 7 kV was required to suppress MP reliably [20]. Therefore, further investigations are needed to match numerical and experimental data.…”
Section: A DC Biasing (Static Electric Perturbation)mentioning
confidence: 99%